2006
DOI: 10.1073/pnas.0602979103
|View full text |Cite|
|
Sign up to set email alerts
|

Anomalous levels of Cl transporters in the hippocampal subiculum from temporal lobe epilepsy patients make GABA excitatory

Abstract: The mRNA levels of NKCC1, an inwardly directed Na + , K + -2Cl − cotransporter that facilitates the accumulation of intracellular Cl − , and of KCC2, an outwardly directed K + -Cl − cotransporter that extrudes Cl − , were studied in surgically resected brain specimens from drug-resistant temporal lobe (TL) epilepsy (TLE) patients. Quantitative R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
222
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(246 citation statements)
references
References 21 publications
22
222
0
2
Order By: Relevance
“…NKCC1 mRNA and a downregulation of KCC2 mRNA in the human epileptic subiculum compared with hippocampus and lateral neocortex (Palma et al, 2006). Our results with the antagonist bumetanide (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…NKCC1 mRNA and a downregulation of KCC2 mRNA in the human epileptic subiculum compared with hippocampus and lateral neocortex (Palma et al, 2006). Our results with the antagonist bumetanide (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Depolarization of neurons would bring them closer to AP generation, whereas larger GABA release would increase intracellular chloride accumulation at the beginning of light stimulation, when ChR2-positive interneurons are firing, thereby readily triggering APs in pyramidal neurons. Such a shift in outcome of GABA A receptor activation has been reported for other models of epilepsy (Traub et al, 1995;Barmashenko et al, 2011) and in tissue from human epilepsy patients (Palma et al, 2006;Huberfeld et al, 2007).…”
Section: Activation Of Gad2 Interneurons Inhibits Epileptiform Activitysupporting
confidence: 59%
“…For example, hippocampal neurons from drug resistant temporal lobe epilepsy patients exhibit alterations in the expression of chloride transporters resulting in hyperexcitability (Palma et al 2006) as also observed following cortical injury in pyramidal neurons (Jin et al 2005), and astrocytes increase their resting chloride conductance in the case of reactive gliosis (MacVicar et al 1989;Walz and Wuttke 1999). Additionally, cells of the major primary brain tumors, gliomas, have a significant resting conductance for Cl Ϫ , which has been shown to be important for both the extensive proliferation and invasive migration of these cells (Habela and Sontheimer 2007;).…”
Section: Introductionmentioning
confidence: 99%